Primary cerebral lymphoma. Mental disorders after biopsy (case report) - N. P. Ilyaev; O. A. Maksakova; O. S. Zaitsev; D. I. Pitskhelauri; A. P. Troitskiy; G. L. Kobiakov; A. A. Poddubskiy; S. A. Maryashev; A. E. Bykanov (Архивъ внутренней медицины)
The article reviews the literature on the diagnosis and treatment of primary lymphomas of the central nervous system and describes a case of mental disorder before and after surgery in a patient with lymphoma of the third ventricle. Using an interdisciplinary approach, psychopathological dynamics is analyzed taking into account the structural and functional state of the brain, which allowed to clarify the possible causes of mental disorders and methods of treatment. Acute onset of confusion and headache was associated with disorders of the liquor outflow, due to the localization of the tumor. The reason for the disintegration of consciousness after surgery was brain hypoxia and the instability of connections between cerebral structures associated with it. The peculiarity of the consciousness recovery could be determined by premorbid personal traits.